Identifying Patterns of Meta-Emotional Beliefs in Emotionally Suppressed Women - Oliveira, Mariana (Psychology of Woman Journal, 2025)
Objective: This study aimed to explore the underlying patterns of meta-emotional beliefs in emotionally suppressed women and understand how these beliefs influence emotional regulation and interpersonal behavior. Methods and Materials: Using a qualitative research design, 26 women from Spain who self-identified as emotionally suppressed were interviewed through semi-structured, in-depth conversations. Participants were recruited through purposive sampling, and interviews continued until theoretical saturation was achieved. Data were transcribed verbatim and analyzed using thematic analysis within a constructivist framework, supported by NVivo 14 software. Coding followed Braun and Clarke’s six-phase approach, identifying key themes, subthemes, and concepts that reflect participants’ beliefs and strategies related to emotional suppression. Findings: Analysis revealed four major themes: (1) Internalized Emotional Norms, encompassing cultural, familial, and moral beliefs that discourage emotional expression; (2) Emotional Self-Evaluation, involving shame, guilt, and perfectionistic beliefs about emotional experience; (3) Interpersonal Emotional Dynamics, reflecting fears of rejection, emotional burdening, and conditional disclosure; and (4) Adaptive and Maladaptive Coping Strategies, including suppression, distraction, intellectualization, and emotional masking. Participants consistently reported beliefs that emotions were dangerous, untrustworthy, or inappropriate, and these beliefs shaped both their intrapersonal experiences and relational behaviors. Conclusion: The findings suggest that emotional suppression in women is underpinned by complex, internalized meta-emotional beliefs formed through sociocultural, familial, and relational influences. These beliefs contribute to rigid emotional regulation strategies that prioritize control and social acceptance over emotional authenticity.